w WANPRESTASI PELAKSANAANuPERJANJIANuKERJASAMA WANPRESTASI PELAKSANAAN PERJANJIAN KERJASAMA PEMBANGUNAN PERUMAHAN GRIYA PURI HUSADA ANTARA PEMILIK TANAH DENGAN PENGEMBANG (DEVELOPER): kerjasama, pelaksanaan kerjasama, hambatan kerjasama - Pohan, Zulfikri (UIR Law Review, 2024)
The Griya Puri Husada housing development cooperation agreement is between the landowner and the developer who has entered into a cooperation agreement and is stated in adeed of cooperation agreement made before a Notary. Each party's rights and obligationshave been agreed upon by both parties and must be implemented as appropriate. The firstparty is the owner of the plot of land and the second party is the developer who builds andmanages the housing. Every house sold from every house deal makes a profit. The secondparty only completes the work until it is completed no later than 2 years even though afterthat time period the land owner's rights have not been fulfilled. This research method islegal research using empirical legal methods. Data sources were obtained from the firstparty or land owner and the second party or developer as well as library data such asstatutory regulations, books, journals and articles related to research. This research wascarried out at the research location in the Griya Puri Husada housing complex. This paperconcludes that: (1). The implementation of the cooperation agreement did not run as itshould, the second party did not carry out the housing development as it should by buildingand managing the construction within two years at the latest. (2). The second party also hasnot paid the full amount to the first party or land owner. The second party or developerexperiences obstacles in the early stages such as permits and correspondence, as well asfinding consumers or buyers quickly.